HIV/AIDS in Indonesia: current treatment landscape, future therapeutic horizons, and herbal approaches - Jocelyn,; Nasution, Fadli Mubaroq; Nasution, Natasya Assyifa; Asshiddiqi, M. Hanafi; Kimura, Nidya Haschita; Siburian, Madeline Hana Tasya; Rusdi, Zata Yumni Nabila; Munthe, Annisa Renzu; Chairenza, Ivina; Ginting Munthe, Michelle C. F. Br.; Sianipar, Putri; Gultom, Surya Perdana; et al. (Frontiers in Public Health, 2024)
HIV/AIDS is still a major worldwide health concern, and Indonesia is making efforts to mitigate its effects. Antiretroviral therapy (ARV), which aims to decrease viral replication, boost immunological function, and lengthen the lifespans of persons living with HIV/AIDS, is the cornerstone of Indonesia’s strategy. The availability of ARV has significantly increased, yet problems including stigma and the requirement for regular medication adherence still exist. To address the broader needs of those affected by HIV/AIDS, Indonesia lays a major focus on comprehensive care, which includes mental health and social support, in addition to ARV. Data show that, despite progress, there is still a stigma surrounding HIV/AIDS, which affects patient outcomes and access to care. With vigorous research into cutting-edge antiretroviral medications and treatment techniques, Indonesia has a thriving future therapeutic landscape. The goals of these programs are to increase treatment effectiveness, decrease side effects, and increase access to cutting-edge treatments. Preventive methods, such as PrEP (pre-exposure prophylaxis), are making progress, and efforts to find a cure are gaining prominence. Notably, HIV/AIDS management plan of Indonesia heavily relies on natural remedies. Patient care incorporates traditional Indonesian medicine, such as jamu and several herbal medicines. Although there is little scientific proof to support the effectiveness of these herbal remedies, complementary and alternative therapies frequently employ them to manage symptoms and promote general wellness. In terms of the 95-95-95 targets, Indonesia is making an effort to comply with these international goals by seeking to diagnose 95% of HIV-positive individuals, provide sustained ARV to 95% of those diagnosed, and achieve viral suppression in 95% of ARV recipients. Although there are gaps in reaching these aims, progress is being made, in part because of the aforementioned challenges. In summary, Indonesia employs a multimodal approach to HIV/AIDS management, including traditional herbal cures, continuous research into cutting-edge treatments, and conventional ARV. In order to enhance overall health outcomes and create a healthier society, the future of HIV/AIDS treatment in Indonesia is concentrated on expanding therapeutic alternatives, reaching the 95-95-95 targets, decreasing stigma, and improving access to care.